A catalyst for dehydrogenating ethylbenzene to produce styrene, and its preparation method and application

By using Fe2O3, K2O, CeO2, WO3, MgO, Na2O catalysts in the ethylbenzene dehydrogenation reaction, especially to increase the exposed crystal surface area of ​​CeO2 (111), the problem of low selectivity and poor stability of the catalyst under low water ratio conditions is solved, and efficient styrene preparation and low production costs are achieved.

CN115957775BActive Publication Date: 2025-04-25CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202111182496.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-10-11
Publication Date
2025-04-25
Estimated Expiration
2041-10-11

AI Technical Summary

Technical Problem

The existing technology for dehydrogenation of ethylbenzene styrene is low in catalyst selectivity and poor stability under low water ratio conditions, resulting in high production costs.

Method used

A catalyst including Fe2O3, K2O, CeO2, WO3, MgO, and Na2O is used, and the exposed crystal surface area of ​​CeO2 (111) accounts for more than 70% of the total exposed crystal surface area. The selectivity and stability of the catalyst are improved through specific preparation methods and calcining conditions.

Benefits of technology

High selectivity of styrene and high stability of catalysts in ethylbenzene dehydrogenation reaction under low water ratio conditions are achieved, reducing production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115957775B_ABST
    Figure CN115957775B_ABST
Patent Text Reader

Abstract

The present invention relates to a catalyst for preparing styrene from ethylbenzene by dehydrogenation, and a preparation method and application thereof. The catalyst comprises Fe2O3, K2O, CeO2, WO3, MgO and Na2O; wherein the exposed crystal surface area of ​​CeO2 (111) accounts for more than 70% of the total exposed crystal surface area of ​​CeO2. The catalyst of the present invention has high selectivity and high stability when used for ethylbenzene dehydrogenation reaction.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a catalyst for preparing styrene by dehydrogenating ethylbenzene, and in particular to a catalyst for preparing styrene by dehydrogenating ethylbenzene with a low water ratio, and a preparation method and application thereof. Background Art

[0002] Styrene monomer is the simplest type in the series of unsaturated aromatic monomers. It is an important raw material for the synthetic rubber and plastics industry and occupies an important position in the national economy. The catalytic dehydrogenation of ethylbenzene has always been the dominant technical route for the production of styrene at home and abroad, and its production capacity accounts for more than 85% of the total production capacity of styrene. In order to improve the production efficiency of ethylbenzene dehydrogenation, a large amount of high-temperature water vapor is usually introduced in the industry. Water vapor plays many important roles in the reaction, such as providing the heat required for the reaction, promoting the chemical equilibrium to move toward styrene, eliminating carbon deposits on the catalyst surface through water-gas shift reaction, and maintaining catalyst activity on the oxidation catalyst surface. However, a large amount of superheated water vapor as a dehydrogenation medium makes the process energy-consuming, the product condensation volume is large, and the process equipment cost is high, resulting in high production costs. It has become an urgent need for styrene enterprises to develop high-selectivity styrene catalysts suitable for low water ratios, so as to achieve energy saving and consumption reduction of styrene units and reduce production costs.

[0003] In the catalytic dehydrogenation reaction of ethylbenzene, toluene and benzene are the main by-products. The by-product benzene can be separated by the distillation unit and returned to the ethylbenzene unit for recycling. However, toluene with low economic value can only be sold at a low price as a by-product. Reducing the amount of toluene produced can improve the utilization rate of the raw material ethylbenzene, reduce the material consumption of the device, and increase economic benefits. Styrene devices give priority to catalysts with good styrene selectivity. Most of the existing styrene catalysts are based on Fe-K-Ce, with Fe-K oxide as the main catalyst and Ce as the main auxiliary agent. They also contain structural stabilizers and electronic auxiliary agents such as oxides of Mg, Mo, W and Ca. The currently disclosed low-water ratio ethylbenzene dehydrogenation catalysts mainly use methods such as improving the structural stability of the catalyst and modifying the surface properties of the catalyst to improve the stability, activity and selectivity of the catalyst under low water ratio conditions. CN106582678A discloses that on the basis of a Fe-K-Ce-W catalyst, by introducing Ba, Sn and rare earth oxides (Sm, Eu, Gd), the active phase of the catalyst is stabilized, and the catalyst has high activity and high stability under low water ratio conditions; CN101279269A discloses a catalyst in which bismuth oxide and beryllium oxide are added to an iron-potassium-cerium-tungsten-calcium catalyst system, which improves the stability and activity of the ethylbenzene dehydrogenation catalyst under low water ratio conditions. The existing production method for ethylbenzene dehydrogenation to styrene still has the problem of insufficient styrene selectivity under low water ratio conditions.

[0004] Today's styrene production technology is developing towards large-scale equipment and comprehensive energy utilization. In order to improve the economic efficiency of ethylbenzene dehydrogenation to styrene, it is necessary to develop an ethylbenzene dehydrogenation catalyst suitable for operation under low water ratio conditions, with high selectivity and better stability. Summary of the invention

[0005] One of the technical problems to be solved by the present invention is that the catalyst has low selectivity and poor stability in the existing technology for preparing styrene by dehydrogenation of ethylbenzene under the condition of low water ratio, and provides a new dehydrogenation catalyst for preparing styrene. The catalyst has high selectivity and high stability for the dehydrogenation reaction of ethylbenzene.

[0006] The second technical problem to be solved by the present invention is to provide a method for preparing an ethylbenzene dehydrogenation catalyst for preparing styrene corresponding to the first technical problem to be solved.

[0007] The third technical problem to be solved by the present invention is to provide an application of an ethylbenzene dehydrogenation catalyst for preparing styrene in the dehydrogenation of ethylbenzene to prepare styrene at a low water ratio, corresponding to the first technical problem to be solved.

[0008] In order to solve one of the above technical problems, the technical solution adopted by the present invention is as follows:

[0009] A first aspect of the present invention provides a catalyst for dehydrogenating ethylbenzene to produce styrene, the catalyst comprising Fe2O3, K2O, CeO2, WO3, MgO, and Na2O; wherein the exposed crystal surface area of ​​CeO2 (111) accounts for more than 70% of the total exposed crystal surface area of ​​CeO2, preferably more than 75%.

[0010] In the above technical solution, the catalyst, based on the total mass of the catalyst, includes the following components by mass fraction:

[0011] (a) 60-85% Fe2O3;

[0012] (b) 6-14% K2O;

[0013] (c) 6-14% CeO2;

[0014] (d) 0.5-5% WO3;

[0015] (e) 0.2 to 5% MgO;

[0016] (f) 0.1-2% Na2O.

[0017] In the above technical solution, preferably, based on the total mass of the catalyst, the catalyst contains 0.01-1.0% of oxides of other metals such as Sm and / or La in terms of mass fraction.

[0018] In the above technical solution, preferably, the exposed crystal surface area of ​​CeO2 (111) accounts for more than 75% of the total exposed crystal surface area of ​​CeO2; for example but not limited to 78%, 80%, 85%, 87%, 90%, 92%, 95%, 97%, 99%, etc.

[0019] To solve the second of the above technical problems, the technical solution adopted by the present invention is as follows:

[0020] The second aspect of the present invention provides a method for preparing the above-mentioned catalyst for dehydrogenating ethylbenzene to produce styrene, comprising the following steps:

[0021] The catalyst is prepared by uniformly mixing Fe source, K source, Ce source, W source, Mg source, Na source and an optional porogen, adding an alkaline solution, standing for reaction, forming and calcining. The alkaline solution is a solution of tert-butylamine and / or ammonia water.

[0022] In the above technical solution, the alkaline solution is a solution of tert-butylamine and / or ammonia water, preferably a solution of tert-butylamine and ammonia water; the mass ratio of ammonia water in terms of NH3·H2O to tert-butylamine in the alkaline solution is preferably 1 to 10:1. The concentration of the alkaline solution is 0.5 to 5 mol / L. In the preparation method of the catalyst, the amount of the alkaline solution is sufficient to ensure that the cerium source is dissolved in the liquid phase for reaction.

[0023] In the above technical scheme, the Fe source is added in the form of oxide Fe2O3. The Fe source is preferably selected from red iron oxide and / or yellow iron oxide, and more preferably a combination of red iron oxide and yellow iron oxide, wherein the mass ratio of red iron oxide and yellow iron oxide, calculated as Fe2O3, is 1.0 to 3.0:1. The K source is added in the form of potassium salt; the potassium salt is selected from any one or more of potassium carbonate, potassium nitrate, and potassium bicarbonate. The Ce source is added in the form of cerium salt; the cerium salt is cerium nitrate. The W source is added in the form of tungsten salt or oxide; the tungsten salt is ammonium tungstate. The Mg source is added in the form of oxide or magnesium salt. The magnesium salt is magnesium carbonate. The Na source is added in the form of sodium salt. The sodium salt is selected from any one or more of sodium carbonate or sodium bicarbonate. The porogen is any one or more of activated carbon, graphite, sodium carboxymethyl cellulose, and polystyrene microspheres. The amount of the porogen added is 0 to 5% of the mass of the catalyst. In the preparation method of the catalyst, the Fe source, K source, Ce source, W source, Mg source, Na source and porogen are all added in the form of solid powder.

[0024] In the above technical solution, the raw material also contains a Sm source and / or a La source; the Sm source and / or the La source are mixed uniformly with a Fe source, a K source, a Ce source, a W source, a Mg source, a Na source, and an optional porogen and added. The Sm source is added in the form of a Sm salt or an oxide; the Sm salt is any one or both of samarium nitrate and samarium chloride. The La source is added in the form of a La salt or an oxide; the La salt is any one or both of lanthanum nitrate and lanthanum chloride.

[0025] In the above technical solution, the mixing can be performed by conventional mechanical stirring method.

[0026] In the above technical solution, the static reaction condition is to statically react at 185-265° C. for 12-48 hours. The static reaction container is preferably an autoclave. The static reaction pressure is not particularly limited.

[0027] In the above technical solution, the molding can be performed by extrusion molding, and the strips can be particles with a diameter of 2 to 5 mm and a length of 3 to 10 mm. If the reacted material cannot meet the molding requirements, some water can be removed by evaporation or an appropriate amount of water can be added before molding.

[0028] In the above technical solution, the calcination temperature is 600-1000° C., and the calcination time is 2-8 hours.

[0029] In the above technical solution, as a preferred calcination condition, a two-step calcination is adopted, for example but not limited to calcination at 600-800° C. for 2-4 hours, and then calcination at 900-1000° C. for 2-4 hours. The calcination is carried out in a muffle furnace.

[0030] In the above technical solution, the formed material may be dried before being calcined at a temperature of 30 to 200° C. for a time of 1 to 24 hours.

[0031] To solve the third technical problem, the third aspect of the present invention provides the use of the above catalyst in the dehydrogenation of ethylbenzene to prepare styrene.

[0032] In the above technical solution, the use of the catalyst in the preparation of styrene is suitable for the dehydrogenation of ethylbenzene with a water ratio of less than 2.0, preferably 1.3 to 2.0.

[0033] In the above technical solution, the use of the ethylbenzene dehydrogenation catalyst in the preparation of styrene is suitable for the dehydrogenation of ethylbenzene under a low water ratio; the low water ratio is below 1.3, preferably 0.7 to 1.3.

[0034] In the above technical solution, the application includes: a raw material containing ethylbenzene is contacted with the above catalyst of the present invention in the presence of water vapor to carry out a dehydrogenation reaction to obtain a product containing styrene.

[0035] In the above technical solution, water is preheated to become water vapor before entering the reactor and is fully mixed with the raw gas.

[0036] In the above technical solution, the temperature of the dehydrogenation reaction is 570-640°C.

[0037] In the above technical solution, the pressure of the dehydrogenation reaction is an absolute pressure of 20 to 100 kPa.

[0038] In the above technical solution, the mass space velocity of ethylbenzene is 0.2~2.0h -1 .

[0039] Compared with the prior art, the present invention has significant advantages and outstanding effects, as follows:

[0040] 1. The crystal face effect of the catalyst has an important influence on the catalytic performance. The inventors have found that the reaction performance of the Fe-K-Ce-W ethylbenzene dehydrogenation catalyst is highly correlated with the surface structure of CeO2 in the catalyst, and different CeO2 exposed crystal faces will lead to significant differences in the catalyst dehydrogenation selectivity and stability. The inventors have further found that the CeO2 (111) exposed crystal face area accounts for more than 70% of the total CeO2 exposed crystal face area, and the catalyst prepared by combining with the main active component of the catalyst, potassium iron, is used in the ethylbenzene dehydrogenation reaction, and has the outstanding advantages of less by-products, high styrene selectivity and good stability.

[0041] 2. In the present invention, the inventors have found through research that by controlling the concentration of alkali in the solution and the wet reaction conditions during the hydrothermal synthesis preparation process, the surface structure of CeO2 in the catalyst can be well controlled, so that the exposed crystal surface of CeO2 (111) accounts for a high proportion, which is conducive to improving the selectivity of the target product styrene in the ethylbenzene dehydrogenation reaction. On the other hand, the preparation method promotes the interaction between the auxiliary component and the active component, and improves the stability of the crystal structure in the catalyst. Compared with the conventional dry preparation, it is more conducive to improving the catalytic performance of the ethylbenzene dehydrogenation catalyst, especially the selectivity. The catalyst preparation process is simple, and the obtained catalyst has the advantages of high selectivity for styrene and stable performance after the catalyst runs for 1000 hours.

[0042] 3. The catalyst of the present invention is used in the dehydrogenation of ethylbenzene to prepare styrene. It has high selectivity and high stability at low to high water ratios, especially at low water ratios, and has achieved good technical effects.

[0043] The catalyst prepared by the present invention is evaluated for activity in an isothermal fixed bed at 70 kPa (absolute pressure) and a liquid space velocity of 1.0 h -1, 620°C, and the water ratio was reduced from the usual 2.0 (weight) to 0.8 (weight), the styrene selectivity can reach more than 96.8%. After running for 1000 hours, the catalyst performance remained stable, and the selectivity did not change significantly. This shows that the catalyst of the present invention significantly improves the selectivity and stability of the catalyst under low water ratio conditions, and achieves good technical effects. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] Figure 1 This is the main exposed crystal plane image of the catalyst obtained in Example 1 tested by HAADF-STEM;

[0045] Figure 2 This is the main exposed crystal plane image of the catalyst obtained in Comparative Example 1 by HAADF-STEM test. DETAILED DESCRIPTION

[0046] The present invention will be further described below by way of examples, but the protection scope of the present invention is not limited by the examples.

[0047] In the present invention, the exposed crystal surface area is tested by high-angle annular dark field scanning transmission electron microscope (HAADF-STEM) characterization method, and the testing instrument is FEI's double spherical aberration corrected Titan Cubed Themis G2 300 transmission electron microscope. The ratio of CeO2 (111) crystal surface to the total exposed crystal surface area of ​​CeO2 is obtained by statistics and calculation based on the HAADF-STEM morphology photos and geometric structure characteristics of the catalyst sample, that is, the ratio of the observed CeO2 (111) crystal surface area to the observed total exposed crystal surface area of ​​CeO2. The total exposed crystal surface area of ​​CeO2 is the sum of the exposed crystal surface areas of CeO2 (100), CeO2 (110), CeO2 (111) and CeO2 (311). The (111) exposed crystal plane was observed by scanning transmission electron microscopy. The interplanar spacing in the plane perpendicular to the (111) observation direction was 305-335 pm, proving that the exposed crystal plane was CeO2 (111).

[0048] In the present invention, the catalyst of the present invention is used to evaluate the performance of ethylbenzene dehydrogenation reaction in an isothermal fixed bed, and the process is briefly described as follows:

[0049] The reactor is a stainless steel tube with an inner diameter of 1", filled with 50-150 ml of catalyst with a diameter of 3-10 mm. Deionized water and ethylbenzene are respectively fed into the preheating mixer through metering pumps, and then preheated and mixed into a gaseous state before entering the reactor. The reactor is heated by an electric heating wire to reach a predetermined temperature. The reactants flowing out of the reactor are condensed with water and their composition is analyzed by a gas chromatograph.

[0050] The ethylbenzene conversion rate and styrene selectivity are calculated according to the following formula:

[0051]

[0052]

[0053] [Example 1]

[0054] Weigh 48.2 parts of red iron oxide equivalent to Fe2O3, 23.6 parts of yellow iron oxide equivalent to Fe2O3, 11.2 parts of potassium carbonate equivalent to K2O, 10.9 parts of cerium nitrate equivalent to CeO2, 1.6 parts of ammonium tungstate equivalent to WO3, 3.6 parts of magnesium oxide, 0.7 parts of sodium carbonate equivalent to Na2O, 0.2 parts of Sm2O3 and 2.8 parts of polystyrene microspheres, and stir in a mixer for 2 hours until the mixture is uniform. Then add 1.9 parts of NH3·H2O and 0.6 parts of

[0055] A mixed aqueous solution of tert-butylamine, in which the total concentration of NH3·H2O and tert-butylamine is 2.4 mol / L. The mixture is allowed to stand and react at 230°C for 20 hours in an autoclave. The mixture is then adjusted for water content, extruded and pelletized to obtain particles with a diameter of 3 mm and a length of 6 mm. The particles are placed in an oven, dried at 80°C for 4 hours, dried at 160°C for 4 hours, and then placed in a muffle furnace, calcined at 650°C for 2 hours, and calcined at 900°C for 2 hours to obtain a finished catalyst. The catalyst composition is listed in Table 1.

[0056] 100 ml of catalyst was loaded into the reactor and heated to 40 ℃ under 70 kPa (absolute pressure) and liquid space velocity of 1.0 h -1 The performance evaluation was carried out under the conditions of temperature 620°C and water ratio 0.8 (wt). The test results of reaction time 100h are listed in Table 1, and the test results of reaction time 1000h are listed in Table 2.

[0057] [Example 2]

[0058] Weigh 38.4 parts of red iron oxide equivalent to Fe2O3, 23.1 parts of yellow iron oxide equivalent to Fe2O3, 13.7 parts of potassium carbonate equivalent to K2O, 13.4 parts of cerium nitrate equivalent to CeO2, 4.9 parts of ammonium tungstate equivalent to WO3, 3.7 parts of magnesium oxide, 1.8 parts of sodium carbonate equivalent to Na2O, 1.0 parts of Sm2O3 and 2.4 parts of polystyrene microspheres, and stir in a mixer for 2 hours until the mixture is uniform. Then add 3.8 parts of NH3·H2O and 0.4 parts of

[0059] A mixed aqueous solution of tert-butylamine, in which the total concentration of NH3·H2O and tert-butylamine is 4.8 mol / L. The mixture is allowed to stand for reaction at 190°C for 48 hours in an autoclave. The mixture is then adjusted for water content, extruded and pelletized to obtain particles with a diameter of 3 mm and a length of 6 mm. The particles are placed in an oven, dried at 80°C for 4 hours, dried at 150°C for 4 hours, and then placed in a muffle furnace, calcined at 650°C for 2 hours, and calcined at 900°C for 2 hours to obtain a finished catalyst. The catalyst composition is listed in Table 1.

[0060] 100 ml of catalyst was loaded into the reactor and heated to 40 ℃ under 70 kPa (absolute pressure) and liquid space velocity of 1.0 h -1 The performance evaluation was carried out under the conditions of temperature 620℃ and water ratio 0.8 (wt%). The test results of reaction for 100h are listed in Table 1.

[0061] [Example 3]

[0062] Weigh 45.2 parts of red iron oxide equivalent to Fe2O3, 25.4 parts of yellow iron oxide equivalent to Fe2O3, 10.3 parts of potassium carbonate equivalent to K2O, 10.5 parts of cerium nitrate equivalent to CeO2, 3.1 parts of ammonium tungstate equivalent to WO3, 4.55 parts of magnesium oxide, 0.9 parts of sodium carbonate equivalent to Na2O, 0.05 parts of Sm2O3 and 0.5 parts of polystyrene microspheres, and stir in a mixer for 2 hours until the mixture is uniform. Then add 1.7 parts of NH3·H2O and 0.5 parts of tert-butylamine in a mixed aqueous solution, and the total concentration of NH3·H2O and tert-butylamine in the mixed aqueous solution is 2.1 mol / L. Let the reaction stand at 260°C in an autoclave for 16 hours. Next, the mixture was adjusted for water content, extruded and pelletized to obtain particles with a diameter of 3 mm and a length of 6 mm. The particles were placed in an oven and dried at 80°C for 4 h and 150°C for 4 h. The particles were then placed in a muffle furnace and calcined at 650°C for 2 h and 900°C for 2 h to obtain the finished catalyst. The catalyst composition is listed in Table 1.

[0063] 100 ml of catalyst was loaded into the reactor and heated to 40 ℃ under 70 kPa (absolute pressure) and liquid space velocity of 1.0 h -1 The performance evaluation was carried out under the conditions of temperature 620℃ and water ratio 0.8 (wt%). The test results of reaction for 100h are listed in Table 1.

[0064] [Example 4]

[0065] Weigh 43.2 parts of red iron oxide equivalent to Fe2O3, 40.5 parts of yellow iron oxide equivalent to Fe2O3, 6.1 parts of potassium carbonate equivalent to K2O, 6.8 parts of cerium nitrate equivalent to CeO2, 2.1 parts of ammonium tungstate equivalent to WO3, 0.2 parts of magnesium oxide, 0.7 parts of sodium carbonate equivalent to Na2O, 0.4 parts of Sm2O3 and 4.6 parts of polystyrene microspheres, and stir in a mixer for 2 hours until the mixture is uniform. Then add 0.6 parts of NH3·H2O and 0.3 parts of tert-butylamine in a mixed aqueous solution, and the total concentration of NH3·H2O and tert-butylamine in the mixed aqueous solution is 0.8 mol / L. Let the reaction stand at 200°C in an autoclave for 40 hours. Next, the mixture was adjusted for water content, extruded and pelletized to obtain particles with a diameter of 3 mm and a length of 6 mm. The particles were placed in an oven and dried at 80°C for 4 h and 150°C for 4 h. The particles were then placed in a muffle furnace and calcined at 650°C for 2 h and 900°C for 2 h to obtain the finished catalyst. The catalyst composition is listed in Table 1.

[0066] 100 ml of catalyst was loaded into the reactor and heated to 40 ℃ under 70 kPa (absolute pressure) and liquid space velocity of 1.0 h -1 The performance evaluation was carried out under the conditions of temperature 620℃ and water ratio 0.8 (wt%). The test results of reaction for 100h are listed in Table 1.

[0067] [Example 5]

[0068] Weigh 56.1 parts of red iron oxide equivalent to Fe2O3, 19.1 parts of yellow iron oxide equivalent to Fe2O3, 8.9 parts of potassium carbonate equivalent to K2O, 8.5 parts of cerium nitrate equivalent to CeO2, 2.6 parts of ammonium tungstate equivalent to WO3, 3.1 parts of magnesium oxide, 0.8 parts of sodium carbonate equivalent to Na2O, 0.9 parts of Sm2O3 and 2.3 parts of polystyrene microspheres, and stir in a mixer for 2 hours until the mixture is uniform. Then add 1.0 parts of NH3·H2O and 0.5 parts of tert-butylamine in a mixed aqueous solution, and the total concentration of NH3·H2O and tert-butylamine in the mixed aqueous solution is 1.2 mol / L. Let the reaction stand at 240°C in an autoclave for 18 hours. Next, the mixture was adjusted for water content, extruded and pelletized to obtain particles with a diameter of 3 mm and a length of 6 mm. The particles were placed in an oven and dried at 80°C for 4 h and 160°C for 4 h. The particles were then placed in a muffle furnace and calcined at 650°C for 2 h and 900°C for 2 h to obtain the finished catalyst. The catalyst composition is listed in Table 1.

[0069] 100 ml of catalyst was loaded into the reactor and heated to 40 ℃ under 70 kPa (absolute pressure) and liquid space velocity of 1.0 h -1 The performance evaluation was carried out under the conditions of temperature 620°C and water ratio 0.8 (wt). The test results of reaction time 100h are listed in Table 1, and the test results of reaction time 1000h are listed in Table 2.

[0070] [Example 6]

[0071] Weigh 47.6 parts of red iron oxide equivalent to Fe2O3, 21.8 parts of yellow iron oxide equivalent to Fe2O3, 12.5 parts of potassium carbonate equivalent to K2O, 12.6 parts of cerium nitrate equivalent to CeO2, 0.5 parts of ammonium tungstate equivalent to WO3, 4.3 parts of magnesium oxide, 0.5 parts of sodium carbonate equivalent to Na2O, 0.2 parts of Sm2O3 and 1.5 parts of polystyrene microspheres, and stir in a mixer for 2 hours until the mixture is uniform. Then add 2.6 parts of NH3·H2O and 0.4 parts of

[0072] A mixed aqueous solution of tert-butylamine, in which the total concentration of NH3·H2O and tert-butylamine is 3.2 mol / L. The mixture is allowed to stand and react at 230°C for 20 hours in an autoclave. The mixture is then adjusted for water content, extruded and pelletized to obtain particles with a diameter of 3 mm and a length of 6 mm. The particles are placed in an oven, dried at 80°C for 4 hours, dried at 150°C for 4 hours, and then placed in a muffle furnace, calcined at 650°C for 2 hours, and calcined at 900°C for 2 hours to obtain a finished catalyst. The catalyst composition is listed in Table 1.

[0073] 100 ml of catalyst was loaded into the reactor and heated to 40 ℃ under 70 kPa (absolute pressure) and liquid space velocity of 1.0 h -1 The performance evaluation was carried out under the conditions of temperature 620℃ and water ratio 0.8 (wt%). The test results of reaction for 100h are listed in Table 1.

[0074] [Example 7]

[0075] Weigh 46.8 parts of red iron oxide equivalent to Fe2O3, 23.2 parts of yellow iron oxide equivalent to Fe2O3, 11.6 parts of potassium carbonate equivalent to K2O, 11.3 parts of cerium nitrate equivalent to CeO2, 2.1 parts of ammonium tungstate equivalent to WO3, 4.3 parts of magnesium oxide, 0.1 parts of sodium carbonate equivalent to Na2O, 0.6 parts of Sm2O3 and 1.2 parts of polystyrene microspheres, and stir in a mixer for 2 hours until the mixture is uniform. Then add 1.8 parts of NH3·H2O and 0.7 parts of

[0076] A mixed aqueous solution of tert-butylamine, in which the total concentration of NH3·H2O and tert-butylamine is 2.2 mol / L. The mixture is allowed to stand and react at 230°C for 20 hours in an autoclave. The mixture is then adjusted for water content, extruded and pelletized to obtain particles with a diameter of 3 mm and a length of 6 mm. The particles are placed in an oven, dried at 80°C for 4 hours, dried at 150°C for 4 hours, and then placed in a muffle furnace, calcined at 650°C for 2 hours, and calcined at 900°C for 2 hours to obtain a finished catalyst. The catalyst composition is listed in Table 1.

[0077] 100 ml of catalyst was loaded into the reactor and heated to 40 ℃ under 70 kPa (absolute pressure) and liquid space velocity of 1.0 h -1The performance evaluation was carried out under the conditions of temperature 620℃ and water ratio 0.8 (wt%). The test results of reaction for 100h are listed in Table 1.

[0078] [Example 8]

[0079] Weigh 45.9 parts of red iron oxide equivalent to Fe2O3, 27.4 parts of yellow iron oxide equivalent to Fe2O3, 9.4 parts of potassium carbonate equivalent to K2O, 10.0 parts of cerium nitrate equivalent to CeO2, 2.5 parts of ammonium tungstate equivalent to WO3, 3.1 parts of magnesium oxide, 1.2 parts of sodium carbonate equivalent to Na2O, 0.5 parts of Sm2O3 and 3.6 parts of polystyrene microspheres, and stir in a mixer for 2 hours until the mixture is uniform. Then add 1.4 parts of NH3·H2O and 1.2 parts of tert-butylamine in a mixed aqueous solution, and the total concentration of NH3·H2O and tert-butylamine in the mixed aqueous solution is 1.8 mol / L. Let the reaction stand at 220°C in an autoclave for 20 hours. Next, the mixture was adjusted for water content, extruded and pelletized to obtain particles with a diameter of 3 mm and a length of 6 mm. The particles were placed in an oven and dried at 80°C for 4 h and 150°C for 4 h. The particles were then placed in a muffle furnace and calcined at 650°C for 2 h and 900°C for 2 h to obtain the finished catalyst. The catalyst composition is listed in Table 1.

[0080] 100 ml of catalyst was loaded into the reactor and heated to 40 ℃ under 70 kPa (absolute pressure) and liquid space velocity of 1.0 h -1 The performance evaluation was carried out under the conditions of temperature 620℃ and water ratio 0.8 (wt%). The test results of reaction for 100h are listed in Table 1.

[0081] [Example 9]

[0082] Weigh 48.7 parts of red iron oxide equivalent to Fe2O3, 24.1 parts of yellow iron oxide equivalent to Fe2O3, 11.8 parts of potassium nitrate equivalent to K2O, 11.2 parts of cerium nitrate equivalent to CeO2, 1.8 parts of WO3, 1.1 parts of magnesium oxide, 1.0 parts of sodium carbonate equivalent to Na2O, 0.3 parts of Sm2O3 and 2.6 parts of polystyrene microspheres, and stir in a mixer for 2 hours until the mixture is uniform. Then add 2.0 parts of NH3·H2O and 0.6 parts of tert-butylamine in a mixed aqueous solution, and the total concentration of NH3·H2O and tert-butylamine in the mixed aqueous solution is 2.5 mol / L. Let the reaction stand at 230°C in an autoclave for 20 hours. Next, the mixture was adjusted for water content, extruded and pelletized to obtain particles with a diameter of 3 mm and a length of 6 mm. The particles were placed in an oven and dried at 80°C for 4 h and 150°C for 4 h. The particles were then placed in a muffle furnace and calcined at 650°C for 2 h and 900°C for 2 h to obtain the finished catalyst. The catalyst composition is listed in Table 1.

[0083] 100 ml of catalyst was loaded into the reactor and heated to 40 ℃ under 70 kPa (absolute pressure) and liquid space velocity of 1.0 h -1The performance evaluation was carried out under the conditions of temperature 620℃ and water ratio 0.8 (wt%). The test results of reaction for 100h are listed in Table 1.

[0084] [Example 10]

[0085] Weigh 44.0 parts of red iron oxide equivalent to Fe2O3, 27.6 parts of yellow iron oxide equivalent to Fe2O3, 10.0 parts of potassium carbonate equivalent to K2O, 12.1 parts of cerium nitrate equivalent to CeO2, 2.2 parts of WO3, 1.8 parts of magnesium carbonate equivalent to MgO, 1.5 parts of sodium bicarbonate equivalent to Na2O, 0.8 parts of samarium nitrate equivalent to Sm2O3 and 2.7 parts of activated carbon, and stir in a mixer for 2 hours until the mixture is uniform. Then add 2.3 parts of NH3·H2O and 0.7 parts of tert-butylamine in a mixed aqueous solution, and the total concentration of NH3·H2O and tert-butylamine in the mixed aqueous solution is 2.9 mol / L. Let the reaction stand at 230°C in an autoclave for 20 hours. Next, the mixture was adjusted for water content, extruded and pelletized to obtain particles with a diameter of 3 mm and a length of 6 mm. The particles were placed in an oven and dried at 80°C for 4 h and 160°C for 4 h. The particles were then placed in a muffle furnace and calcined at 650°C for 2 h and 900°C for 2 h to obtain the finished catalyst. The catalyst composition is listed in Table 1.

[0086] 100 ml of catalyst was loaded into the reactor and heated to 40 ℃ under 70 kPa (absolute pressure) and liquid space velocity of 1.0 h -1 The performance evaluation was carried out under the conditions of temperature 620°C and water ratio 0.8 (wt). The test results of reaction time 100h are listed in Table 1, and the test results of reaction time 1000h are listed in Table 2.

[0087] [Example 11]

[0088] Weigh 48.2 parts of red iron oxide equivalent to Fe2O3, 23.6 parts of yellow iron oxide equivalent to Fe2O3, 11.2 parts of potassium carbonate equivalent to K2O, 10.9 parts of cerium nitrate equivalent to CeO2, 1.6 parts of ammonium tungstate equivalent to WO3, 3.6 parts of magnesium oxide, 0.7 parts of sodium carbonate equivalent to Na2O, 0.2 parts of La2O3 and 2.8 parts of hydroxymethyl cellulose, and stir in a mixer for 2 hours until the mixture is uniform. Then add 1.9 parts of NH3·H2O and 0.6 parts of

[0089] A mixed aqueous solution of tert-butylamine, in which the total concentration of NH3·H2O and tert-butylamine is 2.4 mol / L. The mixture is allowed to stand and react at 230°C for 20 hours in an autoclave. The mixture is then adjusted for water content, extruded and pelletized to obtain particles with a diameter of 3 mm and a length of 6 mm. The particles are placed in an oven, dried at 80°C for 4 hours, dried at 160°C for 4 hours, and then placed in a muffle furnace, calcined at 650°C for 2 hours, and calcined at 900°C for 2 hours to obtain a finished catalyst. The catalyst composition is listed in Table 1.

[0090] 100 ml of catalyst was loaded into the reactor and heated to 40 ℃ under 70 kPa (absolute pressure) and liquid space velocity of 1.0 h -1 The performance evaluation was carried out under the conditions of temperature 620℃ and water ratio 0.8 (wt%). The test results of reaction for 100h are listed in Table 1.

[0091] [Example 12]

[0092] Weigh 48.2 parts of red iron oxide equivalent to Fe2O3, 23.6 parts of yellow iron oxide equivalent to Fe2O3, 11.2 parts of potassium carbonate equivalent to K2O, 10.9 parts of cerium nitrate equivalent to CeO2, 1.6 parts of ammonium tungstate equivalent to WO3, 3.6 parts of magnesium oxide, 0.7 parts of sodium carbonate equivalent to Na2O, 0.2 parts of Sm2O3 and 2.8 parts of polystyrene microspheres, and stir in a mixer for 2 hours until the mixture is uniform. Then add 2.5 parts of NH3·H2O aqueous solution, wherein the concentration of NH3·H2O is 2.4 mol / L. Stand and react in an autoclave at 230°C for 20 hours. Next, the mixture was adjusted for water content, extruded and pelletized to obtain particles with a diameter of 3 mm and a length of 6 mm. The particles were placed in an oven and dried at 80°C for 4 h and 160°C for 4 h. The particles were then placed in a muffle furnace and calcined at 650°C for 2 h and 900°C for 2 h to obtain the finished catalyst. The catalyst composition is listed in Table 1.

[0093] 100 ml of catalyst was loaded into the reactor and heated to 40 ℃ under 70 kPa (absolute pressure) and liquid space velocity of 1.0 h -1 The performance evaluation was carried out under the conditions of temperature 620℃ and water ratio 0.8 (wt%). The test results of reaction for 100h are listed in Table 1.

[0094] [Example 13]

[0095] Weigh 48.2 parts of red iron oxide equivalent to Fe2O3, 23.6 parts of yellow iron oxide equivalent to Fe2O3, 11.2 parts of potassium carbonate equivalent to K2O, 10.9 parts of cerium nitrate equivalent to CeO2, 1.6 parts of ammonium tungstate equivalent to WO3, 3.6 parts of magnesium oxide, 0.7 parts of sodium carbonate equivalent to Na2O, 0.2 parts of Sm2O3 and 2.8 parts of polystyrene microspheres, and stir in a mixer for 2 hours until the mixture is uniform. Then add 2.5 parts of an aqueous solution of tert-butylamine, wherein the concentration of tert-butylamine is 2.4 mol / L. Stand and react at 230°C in an autoclave for 20 hours. Then adjust the water content of the above mixture, extrude and pelletize to obtain particles with a diameter of 3 mm and a length of 6 mm, put them into an oven, dry them at 80°C for 4 hours, dry them at 160°C for 4 hours, then place them in a muffle furnace, roast them at 650°C for 2 hours, and roast them at 900°C for 2 hours to obtain the finished catalyst. The catalyst composition is listed in Table 1.

[0096] 100 ml of catalyst was loaded into the reactor and heated to 40 ℃ under 70 kPa (absolute pressure) and liquid space velocity of 1.0 h -1 The performance evaluation was carried out under the conditions of temperature 620°C and water ratio 0.8 (wt). The test results of reaction time 100h are listed in Table 1, and the test results of reaction time 1000h are listed in Table 2.

[0097] [Comparative Example 1]

[0098] Weigh 48.2 parts of red iron oxide equivalent to Fe2O3, 23.6 parts of yellow iron oxide equivalent to Fe2O3, 11.2 parts of potassium carbonate equivalent to K2O, 10.9 parts of cerium nitrate equivalent to CeO2, 1.6 parts of ammonium tungstate equivalent to WO3, 3.6 parts of magnesium oxide, 0.7 parts of sodium carbonate equivalent to Na2O, 0.2 parts of Sm2O3 and 2.8 parts of polystyrene microspheres, add the same amount of water as in Example 1 in a mixer and stir for 2 hours until the mixture is uniform, and then stand in an autoclave at 230°C for 20 hours. Then adjust the water content of the above mixture, extrude and pelletize to obtain particles with a diameter of 3 mm and a length of 6 mm, put them into an oven, dry them at 80°C for 4 hours, dry them at 160°C for 4 hours, then put them in a muffle furnace, roast them at 650°C for 2 hours, and roast them at 900°C for 2 hours to obtain a finished catalyst, the catalyst composition is listed in Table 1.

[0099] 100 ml of catalyst was loaded into the reactor and heated to 40 ℃ under 70 kPa (absolute pressure) and liquid space velocity of 1.0 h -1 The performance evaluation was carried out under the conditions of temperature 620°C and water ratio 0.8 (wt). The test results of reaction time 100h are listed in Table 1, and the test results of reaction time 1000h are listed in Table 2.

[0100] Table 1 Catalyst compositions, properties and evaluation results of Examples and Comparative Examples

[0101]

[0102] Note: * Ethylbenzene conversion and styrene selectivity after 100h reaction at water ratio of 0.8;

[0103] **Crystal face ratio: The ratio of the exposed crystal face area of ​​CeO2(111) to the total exposed crystal face area of ​​CeO2 in the catalyst.

[0104] Table 2 Catalyst stability evaluation results of Examples and Comparative Examples

[0105]

[0106] from Figure 1 and Figure 2It can be seen that the main exposed crystal face of CeO2 in the catalyst of Example 1 is the CeO2 (111) crystal face. The main exposed crystal face of CeO2 in the catalyst of Comparative Example 1 is the CeO2 (110) crystal face, and the proportion of CeO2 (110) crystal face to the total exposed crystal face of CeO2 is 62%. Combining the results of Table 1 and Table 2, it can be seen that the catalyst of the present invention has high selectivity and good stability. After the dehydrogenation reaction has been running for a long time for 1000 hours, the selectivity of ethylbenzene has not decreased significantly.

[0107] The above describes the specific implementation of the present invention in detail, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the various technical features being combined in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A catalyst for dehydrogenating ethylbenzene to produce styrene, characterized in that: The catalyst comprises Fe2O3, K2O, CeO2, WO3, MgO and Na2O; wherein the exposed crystal surface area of ​​CeO2 (111) accounts for more than 70% of the total exposed crystal surface area of ​​CeO2; The catalyst comprises the following components by mass fraction based on the total mass of the catalyst: (a) 60-85% Fe2O3; (b) 6-14% K2O; (c) 6-14% CeO2; (d) 0.5-5% WO3; (e) 0.2-5% MgO; (f) 0.1-2% Na2O; Based on the total mass of the catalyst, the catalyst contains 0.01-1.0% of Sm and / or La metal oxides in terms of mass fraction.

2. The catalyst according to claim 1, characterized in that: The exposed crystal surface area of ​​CeO2(111) accounts for more than 75% of the total exposed crystal surface area of ​​CeO2.

3. The method for preparing the catalyst according to any one of claims 1 to 2, characterized in that: The following steps are involved: The Fe source, K source, Ce source, W source, Mg source, Na source and an optional porogen are uniformly mixed, and then an alkaline solution is added, and the mixture is allowed to stand for reaction, formed, and calcined to obtain the catalyst; The alkaline solution is a solution of tert-butylamine and / or aqueous ammonia.

4. The preparation method according to claim 3, characterized in that: The concentration of the alkaline solution is 0.5-5 mol / L.

5. The preparation method according to claim 4, characterized in that: The alkaline solution is a solution of tert-butylamine and ammonia water.

6. The preparation method according to claim 5, characterized in that: The mass ratio of ammonia water (calculated as NH3·H2O) to tert-butylamine is 1 to 10:

1.

7. The preparation method according to claim 3, characterized in that: The static reaction condition is to react at 185-265° C. for 12-48 hours.

8. The preparation method according to claim 3, characterized in that: The calcination temperature is 600-1000° C., and the calcination time is 2-8 hours.

9. The preparation method according to any one of claims 3 to 8, characterized in that: The Ce source is cerium nitrate; And / or, the Fe source is added in the form of oxide Fe2O3; And / or, the K source is added in the form of potassium salt; And / or, the W source is added in the form of tungsten salt or oxide; And / or, the Mg source is added in the form of oxide or hydroxide; And / or, the Na source is added in the form of sodium salt.

10. Use of the catalyst according to any one of claims 1 to 2 or the catalyst prepared by the preparation method according to any one of claims 3 to 9 in the dehydrogenation of ethylbenzene to prepare styrene.

11. The use according to claim 10, characterized in that: The catalyst is suitable for ethylbenzene dehydrogenation under low water ratio; the low water ratio is below 1.

3.

12. The use according to claim 11, characterized in that: The catalyst is suitable for ethylbenzene dehydrogenation under low water ratio; the low water ratio is 0.7-1.3.

Citation Information

Patent Citations

  • Low water ratio catalyst for preparing phenylethylene from dehydrogenation of phenylethane

    CN101279269A

  • High-activity and low-water-ratio ethylbenzene dehydrogenation catalyst

    CN106582678A

  • Catalyst for ethylbenzene dehydrogenation in low steam to ethylbenzene ratio, preparation method and application thereof

    CN110681390A

  • Ethylbenzene dehydrogenation catalyst with low vapor to ethylbenzene ratio, and preparation method and application thereof

    CN110681393A